Exploring Critical Thinking through AI Educational Tools:The Case Study of Third Year Students at Sadek Talbi Secondary School Laghouat - Benalia ,Massouda; Boumédiène, Houda (Faculty of Letters and Foreign Languages Department of English, 2025)
With the wider application of Artificial Intelligence (AI) in education, there are increasing concerns over its impact on students' critical thinking. This study investigates how third-year EFL students at SADEK TALBI Secondary School in Laghouat use AI tools, and to Which this encourages or hinders their independent thinking. As students more and more rely on AI for writing, translation, and research, the question is then asked about whether they can still analyze, question, and generate ideas without the use of technology. A mixed-methods design was used, combining a survey given to 20 purposively selected students and 03 teacher interviews to determine the perceived impact of AI on learning behavior and classroom participation. Main findings reflect a dual impact: as students largely attribute AI to assist them in grasping intricate concepts and enhancing writing—aspects of critical thinking—others manifest evidence of passivity, using AI-generated work without question or validation. The study concludes that AI can only be helped with critical thinking if it is put into practice with intention and trained guidance. It recommends that teachers incorporate AI into lessons with well-stated analytical goals, and both students and teachers must be trained to use AI ethically